CAKUT subtypes determine the rate of progression to kidney failure: an adult patient cohort study - Hammett, Charlotte; Petzold, Friederike; Stopp, Sarah; Brigl, Carolin B; Münch, Johannes; Jens, Annika; Yealland, Guy; Popp, Bernt; Eckardt, Kai-Uwe; Budde, Klemens; Schrezenmeier, Eva; de Fallois, Jonathan; et al. (Nephrology, dialysis, transplantation, 2025)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the leading cause of paediatric kidney failure (KF) and a significant contributor to KF in adults. Progression to KF varies widely. Early renal risk stratification is challenging due to a lack of data on long-term kidney outcomes during adulthood. This multicentre study aims to correlate progression to KF with CAKUT phenotypes, including the extent of extrarenal involvement and genetic findings.We conducted an observational, retrospective cohort study. A total of 229 adult CAKUT patients with KF either before or after the age of 18 years were recruited at two tertiary care centres. Genetic testing was performed in 117 patients.Genetic testing identified pathogenic variants in 14 patients (12.0%), spanning 10 genes. Extrarenal manifestations were more common in genetically resolved cases [9/14 (64.3%)], primarily affecting the genital [3/14 (21.4%)] and gastrointestinal systems [5/14 (35.7%)]. Syndromic patients experienced significantly earlier KF onset {median age 22.0 years [interquartile range (IQR) 14.0-31.0], n = 81} as compared to those with isolated CAKUT [28.0 years (IQR 21.0-38.0), n = 145]. Among CAKUT subtypes, multicystic dysplastic kidneys presented with the fastest rate of progression to KF [median age at KF onset 18.0 years (IQR 5.0-23.0), n = 9], whereas horseshoe or ectopic kidneys showed more attenuated outcomes [55.5 years (IQR 47.3-62.5), n = 4]. Bilateral kidney and urinary tract involvement was associated with a significantly worse prognosis [median age at KF onset 22.0 years (IQR 15.5-30.0), n = 143] compared with unilateral involvement [37.0 years (IQR 28.0-47.0), n = 71].CAKUT is genetically heterogeneous and the majority of cases remain genetically unresolved. Among patients on kidney replacement therapy, the rate of progression to KF is influenced by extrarenal presentation, bilateral kidney and urinary tract involvement and CAKUT subtype. Comprehensive interdisciplinary phenotypic characterization is essential and also contributes to a more accurate determination of kidney prognosis.
Vorab online veröffentlicht: 27. August 2025
Gesehen am 27.01.2026